Long Noncoding RNA LINC00261 Reduces Proliferation and Migration of Breast Cancer Cells via the NME1-EMT Pathway - Guo G; Dai S; Chen Q (Cancer Management and Research, 2020)
Guangxiu Guo,* Sujuan Dai,* Qing Chen Department of Pathology, The People’s Hospital of Ganzhou, Gannan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guangxiu GuoDepartment of Pathology, The People’s Hospital of Ganzhou, 18 Meiguan Road, Gannan 341000, People’s Republic of ChinaEmail drguangxiuguo@163.comObjective: Long noncoding RNAs (lncRNAs) are emerging as a class of important biological regulators. lncRNAs participate in diverse biological functions and disease processes, especially those leading to tumorigenesis. In this study, we investigate the role of linc00261 in the pathogenesis of breast cancer.Methods: linc00261 and NME1 expression levels were determined in breast cancer tissue and adjacent normal tissue using qRT-PCR. Cell proliferation and migration were analyzed using MTT and transwell assays, respectively. Epithelial–mesenchymal transition markers were examined via Western blotting assay. RNA pull-down was used to examine the interaction between linc00261 and the NME1 mRNA transcript.Results: linc00261 is expressed in lower levels on breast cancer tissues than in para-carcinoma tissues. Reintroduction of linc00261 can inhibit the migration of breast cancer cells and arrest their proliferation. Additionally, linc00261 knockdown is sufficient to cause breast carcinoma tumorigenesis. We also found that linc00261 interacts with NME1 mRNA, protecting it from degradation. This protection leads to increased cellular levels of NME1, which functions as suppressor of tumor metastasis.Conclusion: Taken together, these data demonstrate detailed mechanistic links between the linc00261/NME1 axis and tumorigenesis and show that linc00261 might serve as a novel therapeutic target.Keywords: linc00261, NME1, breast cancer, E-cadherin, N-cadherin